tSocial Capital of Sweet Potato Farmers and Collector Traders in Aki Jaya Village, West Bula District, East Seram Regency - Agung Basuki Litiloli; A.E Pattiselano; Jeter Donald Siwalette (International Journal of Economics, Business and Innovation Research, 2024)
Social Capital of Sweet Potato Farmers and Collector Traders in Aki Jaya Village, West Bula District, East Seram Regency guided by A.E. Pattiselanno and Jeter Donald Siwalette This research aims to find out the social capital of sweet potato farmers and collecting traders. This research was conducted in Aki Jaya Village from October to November 2023. The respondents were 30 people who work as sweet potato farmers and 10 respondents as collecting traders. Data collection was carried out by interviews and using questionnaires and then using qualitative descriptive analysis. The results of this research show that farmers and traders in Aki Jaya Village both benefit from each other in buying and selling and help each other in farming and obey each other's mutually agreed rules.